Forest management decentralization in Kenya: Effects on household farm forestry decisions in Kakamega - Nyangena, W.; Ogada, Maurice Juma; Sikei, G. (2011)
This study investigates the effects of forest decentralization through the Kenya Forest Act of 2005, on farm forestry investment decisions. The study uses household-level data collected from Kakamega forest communities in March, 2010, and controls for selection bias arising from incidental truncation by means of Heckman two-step approach. Our results reveal that participatory forest management, among other factors, significantly reduces the level of farm forestry investment among the poor rural households. This indicates that, although co-management is useful in protecting the existing government forests, a cocktail of other measures must accompany it for increased forest cover to be realized. These measures could include: increased farmer education, introduction of high-value fast-maturing farm trees and farm forestry incentive schemes.